Case Conceptualizing in Acceptance and Commitment Therapy for Moral Injury: An Active and Ongoing Approach to Understanding and Intervening on Moral Injury - Borges, Lauren M.; Barnes, Sean M.; Farnsworth, Jacob K.; Drescher, Kent D.; Walser, Robyn D. (Frontiers in Psychiatry, 2022)
Acceptance and Commitment Therapy for Moral Injury (ACT-MI; 10-11), is an application of Acceptance and Commitment Therapy principles designed to help individuals live their values, even in the presence of moral pain. ACT-MI differs from other emerging treatments for moral injury in that ACT-MI is not based on a traditional syndromal approach to conceptualizing moral injury, which treats moral injury as a collection of signs and symptoms to be reduced. Rather than assuming moral injury causes suffering through a constellation of symptoms that a person has, in ACT-MI, moral injury is defined by what a person does in response to moral pain. Consistent with this framework, we present a unique approach to moral injury case conceptualization that emphasizes function over form, providing clients the opportunity to break free from the patterns of behavior that cause moral injury-related suffering to persist. Rooted in approaches to conceptualizing that have demonstrated utility in extant interventions (e.g., ACT), ACT-MI clinicians conduct ongoing functional analyses to inform case conceptualization and intervention. Functional analysis is used to disrupt the processes maintaining moral injury, as the client and therapist work to identify and intervene on the behaviors reinforcing avoidance and control of painful internal experiences causing moral injury. In the current paper, we guide the reader through a framework for applying functional analysis to the conceptualization of moral injury where the reinforcers driving moral injury are explored. Case examples based on our experiences treating moral injury are presented to demonstrate how various types of morally injurious events can evoke different features of moral pain which in turn motivate different repertoires of avoidance and control. We discuss how to work with moral injury using functional analysis to guide treatment decisions, matching interventional processes within ACT-MI to the specific functions that moral injury-related behavior is serving for an individual. We suggest that the use of functional analytic case formulation procedures described herein can assist clients in disrupting behavioral patterns maintaining moral injury and thereby free them to pursue lives of greater meaning and purpose.